The Framework Nations Concept: Germany's contribution to a capable European defence - Claudia Major; Christian Mölling (Stiftung Wissenschaft und Politik (SWP), 2014)
With the Framework Nations Concept, which it introduced to NATO in 2013, Germany attempted to bring the topic of defence cooperation among NATO countries once more to the foreground. The development of multinational units would, in theory, increase sustainability and help preserve military key capabilities. Smaller armies could plug their remaining capabilities into an organizational backbone provided by a larger, "framework" nation. Politically, the concept represents a step towards transatlantic burden sharing. As the initiator of the concept, Germany must now not only show that the well understood obstacles to defence cooperation can be overcome; it must above all else reduce scepticism among those who would like to cooperate, but doubt Berlin's reliability as a military partner. (SWP Comments)
Keywords: 320